FEATURES OF DEVELOPMENT AND STATE REGULATION OF HUMAN CAPITAL IN THE CONDITIONS OF DIGITAL TRANSFORMATION - TULCHYNSKA, Svitlana; TULCHYNSKYI, Rostyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates that state regulation of human capital in the conditions of digital transformation acquires special importance, since it requires the adaptation of educational programs, the system of professional training and employment policy to new challenges and opportunities arising in the digital economy. The purpose of the article is to identify the features of development and state regulation of human capital in the conditions of digital transformation. The essence of the concept of "human capital" and its differences from other types of capital are clarified. It is proposed to see human capital as formed, accumulated and developed as a result of investing in knowledge, skills, social, cultural psychophysical and other abilities, competencies and other factors of the productive qualities of an individual, which are used by them in socio-economic activities and aimed at reproducing expanded capital. The negative manifestations that have arisen in the development of human capital as a result of military operations in Ukraine are highlighted, including emigration processes, the emergence of needs for specialists with new competencies capable of working in conditions of war and post-war reconstruction, increasing the importance of social responsibility, employment and integration of human capital of displaced persons, reintegration of veterans after the end of hostilities. The impact of digital transformation on the development of intellectual capital is proven, taking into account the aspect that in modern business conditions, knowledge and skills related to digitalization become not only a competitive advantage, but also a necessity for successful activity in all areas of the economy. The directions of state regulation of human capital development in the context of digital transformation are outlined, in the direction of: continuous learning and adaptability, rapid adaptation of the higher education system to the requirements of digitalization, initiation and support of knowledge and experience exchange programs, development and implementation of programs to solve such economic problems as unemployment, poverty and social inequality, ensuring equal access of all citizens to high-quality medical services, stimulating remote forms of organizing entrepreneurial activity.
Keywords: human capital; transformational changes; digital transformation; digitalization; state regulation of human capital; human capital development